1988
DOI: 10.1111/j.1558-5646.1988.tb04138.x
|View full text |Cite
|
Sign up to set email alerts
|

The Consequences of Brood Size for Breeding Blue Tits. Iii. Measuring the Cost of Reproduction: Survival, Future Fecundity, and Differential Dispersal

Abstract: Abstract. -To determine how the cost of reproduction varies with brood size, a population of blue tits (Parus caeruleus) breeding in Wytham Wood, England, was manipulated over a three year period. Two hundred sixteen pairs were randomly assigned 3, 6, 9, 12, or 15 nestlings; nestlings were exchanged soon after hatching. Survival of adult females (as measured by the proportion recaptured in the following winter and/or spring) declined significantly with increasing brood size in two out ofthree years; there was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(68 citation statements)
references
References 46 publications
(54 reference statements)
1
67
0
Order By: Relevance
“…The Blue Tit study cited above (Nur 1988) also revealed an effect of brood size on future reproductive success of adults: the number of offspring produced that survived at least 3 months after fledging was inversely proportional to the experimental brood size the year before (p < 0.05). This effect was expressed in both males and females and in each year of the study (Nur 1988).…”
Section: Review Of Field Studies: Experimental Manipulationsmentioning
confidence: 97%
See 3 more Smart Citations
“…The Blue Tit study cited above (Nur 1988) also revealed an effect of brood size on future reproductive success of adults: the number of offspring produced that survived at least 3 months after fledging was inversely proportional to the experimental brood size the year before (p < 0.05). This effect was expressed in both males and females and in each year of the study (Nur 1988).…”
Section: Review Of Field Studies: Experimental Manipulationsmentioning
confidence: 97%
“…This effect was due principally to a difference in hatching success between the two groups. even moderate distances (~300 m) was apparently rare among females (Nur 1988).…”
Section: Review Of Field Studies: Experimental Manipulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Lack's original argument has received some con£icting evidence, and has been re¢ned over the years (e.g. Ho« gstedt 1980; Boyce & Perrins 1987;Nur 1988), limiting food resources has been widely accepted as one of the most important factors a¡ecting life-history evolution in birds (reviewed in Martin (1987) and Boutin (1990)). Lack (1948) urged researchers to test his hypothesis also in free-ranging mammals, but such experiments have been few.…”
Section: Introductionmentioning
confidence: 99%